Penerapan Media Audio Visual untuk Meningkatkan Kemampuan Menulis Puisi Pada Kelas VII - Samiyatun Samiyatun (Dharmas Education Journal (DE_Journal), 2022)
The problem in this research is, How is the application of audio-visual media in learning to write poetry. The purpose of this study was to determine the application of audio-visual media in learning to write poetry in seventh grade students of SMP Negeri 3 Muara Bungo. This research was carried out in two stages, namely the first cycle stage and the second cycle stage. The subject of this research is the ability to write poetry using direct object technique. Data collection in this study used test and non-test techniques. The test technique is in the form of the results of the ability to write poetry and the non-test technique is in the form of student behavior data from the results of observations. This study uses quantitative data analysis techniques. The technique was analyzed by comparing the results of the test and non-test cycle I and cycle II. The results of this study indicate an increase in the ability to write poetry using audio-visual media. The average value in the first cycle is 72.79. The average value of students in the second cycle is 76.89. While the percentage of completeness in the first cycle was 68.97% and the second cycle was 79.31, this means that this study was not continued to the next cycle because it had reached 75% completeness. Changes in student behavior are also for the better. Based on the results of these studies, the authors suggest that teachers use a variety of media for the progress of learning later.